1999
DOI: 10.3189/002214399793377266
|View full text |Cite
|
Sign up to set email alerts
|

Climate variables along a traverse line in Dronning Maud Land, East Antarctica

Abstract: Temperature, density and accumulation data were obtained from sha]low firn cores, drilled during an overland traverse through a previously unknown part of Dronning Maud Land, East Antarctica. The traverse area is characterised by high mountains that obstruct the ice flow, resulting in a sudden transition from the polar plateau to the coastal region. The spatial variations of potential temperature, ncar-surface firn density and accumulation suggest that katabatic winds are active in this region. Proxy wind data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 7 publications
6
56
0
Order By: Relevance
“…The irregular topography of individual mountain peaks causes the blocking and channelling of the katabatic winds, causing local areas of erosion and deposition of snow. This is evident in the results from a katabatic wind model of surface winds in Dronning Maud Land reported by Van den Broeke et al (1999). Furthermore, Jonsson (1995) showed that the topography of the nunataks also amplifies wind strengths associated with major cyclones centred in the southeastern part of the Weddell Sea.…”
Section: Grounded Coastal Areasmentioning
confidence: 55%
See 2 more Smart Citations
“…The irregular topography of individual mountain peaks causes the blocking and channelling of the katabatic winds, causing local areas of erosion and deposition of snow. This is evident in the results from a katabatic wind model of surface winds in Dronning Maud Land reported by Van den Broeke et al (1999). Furthermore, Jonsson (1995) showed that the topography of the nunataks also amplifies wind strengths associated with major cyclones centred in the southeastern part of the Weddell Sea.…”
Section: Grounded Coastal Areasmentioning
confidence: 55%
“…Probably, the general trend of decreasing accumulation rates on the plateau is related to the capacity of air to retain moisture, which decreases with decreasing temperature and thus increasing elevation (e.g., Robin, 1977). The higher parts of the polar plateau have a relatively smooth net accumulation pattern, except for the section of erosion along the eastern profile (P2) discussed in Richardson and Holmlund (1999) and Van den Broeke et al (1999). Along the western profile, the spatial variability is probably caused by wind redistribution, as it seems to be closely related to the local surface topography.…”
Section: High Polar Plateaumentioning
confidence: 98%
See 1 more Smart Citation
“…cluding Antarctica and Greenland (Cresswell, 1988;Van Den Broeke et al, 1999;Parish and Cassano, 2000;Heinemann and Klein, 2002). Movement of a dense glacial air mass is strongly controlled by the underlying surface terrain and for larger air masses, by Coriolis forces as well.…”
Section: Aeolian Modificationmentioning
confidence: 99%
“…Today the ice sheet is again retreating, increasing the extent of paraglacial landscapes. Recently, ice sheet melt has accelerated (Gordon, 1981;van den Broeke et al, 1999;Krabill et al, 2004). The summer of 2012 was the warmest in recent history setting records for total melt, melt surface extent, and melt season duration (Tedesco et al, 2012).…”
Section: Greenland Ice Sheet Historymentioning
confidence: 99%